La3Ni2SbO9: a relaxor ferromagnet. - Battle, P; Evers, S; Hunter, E; Westwood, M (2013)
A polycrystalline sample of La3Ni2SbO9 has been synthesized using a standard ceramic method and characterized by neutron diffraction and magnetometry. The compound adopts a monoclinic, perovskite-like structure with space group P2(1)/n and unit cell parameters a = 5.0675(1), b = 5.6380(1), c = 7.9379(2) Å, β = 89.999(6)° at room temperature. The two crystallographically distinct six-coordinate sites are occupied by Ni(2+) and a disordered distribution of Ni(2+)/Sb(5+), respectively; the Ni(2+) and Sb(5+) cations occupy the disordered site in a 1:2 ratio. Both ac and dc magnetometry indicate the presence of a spontaneous magnetization below 105 K. A magnetization of 1.5 μB per formula unit was measured at 2 K in a field of 40 kOe. However, no magnetic scattering was observed in neutron diffraction data collected at 5 K. It is proposed that, as a consequence of the cation disorder, La3Ni2SbO9 behaves as a relaxor ferromagnet, analogous to a relaxor ferroelectric, with magnetic domains too small to be detected by neutron diffraction forming below 105 K.